2010
DOI: 10.1021/es903586v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Composition and Domain Arrangement of Biopolymer Components of Soil Organic Matter on the Bioavailability of Phenanthrene

Abstract: Bioavailability of hydrophobic organic compounds (HOCs) is an important factor affecting their fate in the environment. Molecular-level HOC-soil organic matter (SOM) interactions and associated impacts on its bioavailability were investigated in this study. Our results showed that, phenanthrene (PHE) was mainly sequestrated in aromatic domains of lignin, as indicated by liquid-state (1)H-(13)C heteronuclear multiple quantum coherence (HMQC) NMR along with solid-state (13)C NMR data and information on surface d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…The latter possibility seems to be supported by the occurrence of N-containing compounds (average N $ 3.2%) in the LG isolates, which were supposed to contain no N. However, for the degraded lignin, amid functional groups can be added to the aromatic carbon in lignin during humification (Schmidt-Rohr et al, 2004). Moreover, the contents of C and O in the LG isolates were much close to the values for the reported lignin in the other studies, while H contents were slightly higher than their values (Xing et al, 1994;Chefetz et al, 2000;Wang et al, 2007b;Yang et al, 2010). Furthermore, a van Krevelen diagram (Fig.…”
Section: Content and Properties Of Som Fractionssupporting
confidence: 64%
“…The latter possibility seems to be supported by the occurrence of N-containing compounds (average N $ 3.2%) in the LG isolates, which were supposed to contain no N. However, for the degraded lignin, amid functional groups can be added to the aromatic carbon in lignin during humification (Schmidt-Rohr et al, 2004). Moreover, the contents of C and O in the LG isolates were much close to the values for the reported lignin in the other studies, while H contents were slightly higher than their values (Xing et al, 1994;Chefetz et al, 2000;Wang et al, 2007b;Yang et al, 2010). Furthermore, a van Krevelen diagram (Fig.…”
Section: Content and Properties Of Som Fractionssupporting
confidence: 64%
“…As one of the processes in bioremediation, biosorption plays a significant role in the removal of PAHs. In recent studies, biosorption employing microorganisms to eliminate PAHs from the contaminated environment has been proposed (Christensen and Rorrer, 2009;Chen et al, 2010;Yang et al, 2010a;Olivella et al, 2012). Many types of biosorbents (e.g., fungi, bacteria, algae and plant cuticle) were investigated for their ability to sequester heavy metals, dyes, pesticides, and organic pollutants (Aksu, 2005;Chen et al, 2005;Wu and Yu, 2006;Chung et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Bioavailability of dissolved and sorbed HOCs to microorganisms has been identified as major limitation to the effectiveness of bioremediation of contaminated soils [3,7,8,[10][11][12][13][14][15][16][17]. Previous studies have suggested that soil-sorbed HOCs are not directly available for biodegradation without prior desorption to pore water [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that soil-sorbed HOCs are not directly available for biodegradation without prior desorption to pore water [10][11][12]. However, other researchers have shown that sorbed HOCs can be directly degraded by microorganisms via attached cells, or at least that desorption into bulk solution is not a prerequisite for biodegradation [7,[13][14][15][16][17]. Two possible explanations were offered for the experimental observations of bioavailability of soilsorbed HOCs [12,14,18,19].…”
Section: Introductionmentioning
confidence: 99%